THE MEDIATING ROLE OF FLOW ON THE RELATIONSHIP BETWEEN GOAL ORIENTATION AND JOB CRAFTING MODERATED BY EDUCATION LEVEL - Mohd. Asrof Gulam Nabi, 1968-, author; Wan Khairuzzaman Wan Ismail, Prof.Dr., supervisor; Sekolah Pengajian Antarabangsa (Kuala Lumpur : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2017